Exploring the mechanism of acupuncture and moxibustion in the treatment of cerebral ischemia-reperfusion injury based on network pharmacology - Qi, Yunwen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Objective To explore the potential mechanism of acupuncture and moxibustion in the treatment of cerebral ischemia reperfusion injury (CIRI) using network pharmacology. Methods Firstly, the potential targets of acupuncture and moxibustion for CIRI were screened from the GEO database, and then the disease targets of CIRI were screened through data cleaning. Finally, the intersection between the disease targets of acupuncture and moxibustion for CIRI and the disease targets of CIRI were obtained, so as to obtain the key targets of acupuncture and moxibustion for CIRI. The Gene Ontology (GO) and The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed on these key targets. Results A total of 18804 potential CIRI targets, 370 CIRI disease targets and 152 key targets were obtained. GO and KEGG enrichment analysis of the key targets were performed to obtain the most significantly enriched GO entries and key pathways of the targets in cellular components, molecular functions and biological processes. Conclusion Acupuncture and moxibustion may treat CIRI by regulating calcium ion transport, postsynaptic organization and circadian entrainment.